Предмет: Математика,
автор: wewenami2
очень срочно пожалуйста
Приложения:

Ответы
Автор ответа:
0
y=x^(3/5) y'=3/5*x^(3/5-1)=3/5*x^(-2/5)
2. y=(x+5)/x^2=1/x+5/x^2=x^(-1)+5x^(-2)
y'=-1*x^(-2)+5x^(-3)=-1/x^2+5/x^3
2. y=(x+5)/x^2=1/x+5/x^2=x^(-1)+5x^(-2)
y'=-1*x^(-2)+5x^(-3)=-1/x^2+5/x^3
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Українська мова,
автор: ledenev
Предмет: Английский язык,
автор: yoursempai666
Предмет: Математика,
автор: Romik935
Предмет: Физика,
автор: sorkami00